Heroes for the helpless: A critical discourse analysis of Canadian national print media’s coverage of the food insecurity crisis in Nunavut - Bradley Hiebert; Elaine Power (Canadian Food Studies, 2016)
In northern Canada, the Inuit’s transition from a culturally traditional to a Western diet has been accompanied by chronic poverty and provoked high levels of food insecurity, resulting in numerous negative health outcomes. This study examines national coverage of Nunavut food insecurity as presented in two of Canada’s most widely read newspapers: The Globe and Mail and National Post. A critical discourse analysis (CDA) was employed to analyze 24 articles, 19 from The Globe and Mail and 5 from National Post. Analysis suggests national print media propagates the Inuit’s position as The Other by selectively reporting on social issues such as hunger, poverty and income. Terms such as “Northerners” and “Southerners” are frequently used to categorically separate Nunavut from the rest of Canada and Inuit-driven efforts to resolve their own issues are widely ignored. This effectively portrays the Inuit as helpless and the territory as a failure, and allows Canadians to maintain colonialist views of Inuit inferiority and erroneously assume Federal initiatives effectively address Northern food insecurity.